A Conversation with ... Hugo Canuto (A Conversation with ..., 2026)
The interview “A Conversation with … Hugo Canuto” features a discussion between Ute Fendler and Adebanjo Baderin with Brazilian comic artist Hugo Canuto, who visited the University of Bayreuth in mid-May 2025 to participate in the workshop “From Oblivion to Memory: Transatlantic Memorial Echoes.” During the conversation, Hugo Canuto reflects on the role of comics and visual storytelling in preserving cultural memory and reimagining historical narratives. Drawing on Afro-Brazilian mythology, history, and popular culture, he explains how the graphic novel medium allows him to revisit marginalized histories and highlight connections between Africa and the Afro-diasporic world. Canuto also discusses his creative process, emphasizing the importance of visual symbolism, mythology, and narrative experimentation in his work. Find out more about the project "Black Atlantic Revisted" at the Africa Multiple Cluster of Excellence hier: https://www.africamultiple.uni-bayreuth.de/en/1_2-Research/Research-Projects/Arts-and-Aesthetics/Black-Atlantic-revisited/May-Exhibition/index.html